Wacana Non Dominan: Menghadirkan Fikih Alternatif yang Berkeadilan Gender - Sofyan A. P. Kau; Zulkarnain Suleman (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2013)
Jurisprudence has a diversity of opinions over the law interpretation. Among other is the women jurisprudence. Furthermore, the women legal opinion is subsequently not single but diverse. The diversity of women jurisprudence is actually seen as an alternative, that is, ‘gender’ perspective kind of fiqh. This paper offers a non-mainstream discourse over the fiqh by presenting and assessing ‘gender’ perspective kind of jurisprudence. This is done because it is seen that most discourse over women jurisprudence were dominated by gender inequality; and therefore it should be thoroughly criticized. With the exception of akiqah discourses, the way to bath boys’ and girls’ urine, they both treated equally the same. Any physically contacts with women subsequently do not invalidate the ablution (wudhu). Therefore, woman has equal rights with man in custody, witness and leadership. More importantly, in the non-dominant discourse of jurisprudence, woman may be a guardian and a witness to a wedding, even can be a khutbah priest and an imam of public congregational prayers.